Peran Advertising, Brand Image, dan Brand Trust dalam Mempengaruhi Minat Beli Produk Kosmetik Maybelline New York pada Marketplace Shopee - Maulida, Reva Rahma; Sari, Dewi Komala; Hariasih, Misti (Universitas Negeri Padang, 2024)
This study aims to determine the influence of Advertising, Brand Image, and Brand Trust on Purchase Intention of Maybelline New York Cosmetics Products on the Shopee Marketplace in Sidoarjo Regency. The research employed a quantitative method with the population being the residents of Sidoarjo Regency. Nonprobability sampling was used with purposive sampling method, and the number of respondents was 100 people. Data collection was conducted through questionnaire distribution using a Likert scale. The data analysis technique used multiple linear regression with the assistance of Statistical Package for the Social Sciences version 26.0 for Windows. The research findings indicate that Advertising, Brand Image, and Brand Trust individually have a positive influence on the purchase intention of Maybelline New York products in Sidoarjo Regency